THE INFLUENCE OF WORK MOTIVATION, COMPETENCE, AND WORK ENVIRONMENT ON WORKER PERFORMANCE AT PT XYZ - Devi Triana; Samsuri; Palahudin (Fakultas Ekonomi Universitas Djuanda, 2023)
The purpose of this research is to find out and analyze the effect of work motivation, competence, and work environment on the performance of workers of PT XYZ Sales Office either simultaneously or partially. The research design uses descriptive and verification research methods. Sampling technique with saturated sampling method. The number of respondents was 55 people. The subjects of this research are workers of PT XYZ Sales Office and the objects of research are work motivation, competence, work environment, and worker performance. The tools used in this analysis are multiple linear regression analysis, multiple correlation analysis, analysis of the coefficient of determination, and hypothesis testing (F test and t-test). The results of the analysis show that partially or simultaneously, work motivation, competence, and work environment have a positive and significant influence on worker performance at PT XYZ Sales Office.